Representation of Quality Assurance Standards by Faculty members at Jordanian Universities - Khawla Mnawer Aljarrah; Abdullah Mohammed Khataybeh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to identify the degree to which faculty members at Jordanian universities represent quality standards. Methods: To achieve the objectives of the study, we used a descriptive approach. The study data was collected via an online questionnaire whose validity and reliability were verified. The research sample consisted of 250 faculty members from several universities in Jordan. The data was analyzed through descriptive statistics. Results: The results show that the degree of representation of quality assurance standards by faculty members at Jordanian universities was high with a mean of (3.69). There were no statistically significant differences due to academic rank or college for all of the criteria investigated in the study. There were statistically significant differences due to university in all criteria in favor of the University of Science and Technology. Conclusions: This research recommends that universities focus on quality assurance standards by integrating them into their programs and employing them in practice and by encouraging faculty members to abide by these standards.